Rearticulating the Experience of War in Anonyma: Eine Frau in Berlin - Pötzsch, Holger (Nordlit, 2012)
Situating itself in the field of cultural memory studies, this article traces the slow emergence in German historical discourse of the narrative of an anonymous German woman who survived the Soviet occupation of Berlin in 1945. I will, firstly, conceptualize the historical condition of the Anonyma as a precarious liminal sphere of transition between competing sovereignties that dislodged her political status as citizen and reconstituted her as bare life in the sense of Agamben. Secondly, I direct focus to the relationship between the personal story of the Anonyma and a historical Master narrative pertaining to the period. The article argues for a close connection between the woman’s form of resistance that aimed at replacing unchecked rape with a form of coerced prostitution to reassert limited control over the borders of her body, and the negative reception her diary received after a first publication in Germany in 1959. Her story implicitly challenges a hegemonic discourse of war that treats mass rape as mainly an assault on the nation’s male defenders and that silences the victims’ traumatic experiences with reference to collective guilt and individual shame or treason.